2012
DOI: 10.2147/opth.s33414
|View full text |Cite
|
Sign up to set email alerts
|

A randomized crossover study comparing tafluprost 0.005% with travoprost 0.004% in patients with normal-tension glaucoma

Abstract: Purpose:We compared the intraocular pressure (IOP)-lowering effect of tafluprost 0.0015% once daily with travoprost 0.004% once daily in Japanese patients with normal-tension glaucoma (NTG).Methods:One hundred sixteen patients with NTG were randomized to use tafluprost 0.0015% or travoprost 0.004% once daily for 12 weeks, followed by a washout period of 4 weeks between switching medications. IOP was measured at baseline and 4, 8, and 12 weeks of each treatment period.Results:Ninety patients completed both trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
16
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 22 publications
6
16
1
1
Order By: Relevance
“…Previous studies have shown that some patients exhibit a poor response to various PGAs [1113]. Some reports indicate that poor responders to one PGA might respond to another PGA [1315]. In this study, there were no obvious differences of the IOP reduction between patients switched from tafluprost, latanoprost, or travoprost, indicating that Taf–TFC reduces the IOP in patients previously treated with any PGA.…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…Previous studies have shown that some patients exhibit a poor response to various PGAs [1113]. Some reports indicate that poor responders to one PGA might respond to another PGA [1315]. In this study, there were no obvious differences of the IOP reduction between patients switched from tafluprost, latanoprost, or travoprost, indicating that Taf–TFC reduces the IOP in patients previously treated with any PGA.…”
Section: Discussionsupporting
confidence: 44%
“…In this study, the reduction of IOP in patients switched from PGA monotherapy or β-blocker monotherapy was similar to that seen in the phase III studies, confirming superior efficacy of Taf–TFC over PGA or β-blocker monotherapy in this real-world study. Previous studies have shown that some patients exhibit a poor response to various PGAs [1113]. Some reports indicate that poor responders to one PGA might respond to another PGA [1315].…”
Section: Discussionmentioning
confidence: 99%
“…This finding is similar to that of previous studies of patients with normal-tension glaucoma. 29 Kawaguchi et al compared the treatment efficacy of latanoprost, SofZiapreserved travoprost, tafluprost, and bimatoprost using bilateral therapy in normal subjects and showed that the mean diurnal IOP reduction achieved with latanoprost on days 7 and 14 was similar to that observed following treatment with travoprost and tafluprost. 30 One study using an animal model showed that BAK does not affect the corneal penetration of a prostaglandin analog, tafluprost, into rabbit aqueous humor.…”
Section: Discussionmentioning
confidence: 96%
“…Studien, die Kombinationen einzelner Wirkstoffklassen miteinander vergleichen, gibt es hingegen. So scheinen Tafluprost und Travoprost vergleichbar zu sein [29], während die Fix-Kombination von Travoprost plus Timolol etwas wirksamer zu sein scheint als die Fix-Kombination Latanoprost plus Timolol bei gleicher Verträglichkeit [30]. Eine Metaanalyse von Cheng et al [31] hatte zum Ergebnis, dass Latanoprost, Bimatroprost und β-Blocker den IOD am effektivsten in der Therapie des Normaldruckglaukoms zu senken vermochten.…”
Section: Medikamentöse Therapieunclassified